2013
DOI: 10.1159/000350232
|View full text |Cite
|
Sign up to set email alerts
|

Oncological Outcome of Primary versus Secondary Muscle-Invasive Bladder Cancer Is Comparable after Radical Cystectomy

Abstract: Background: High-risk non-muscle-invasive bladder cancer (NMIBC) progressing to muscle-invasive bladder cancer (MIBC) is associated with adverse tumour biology. It is unclear, however, whether outcome of NMIBC progressing to MIBC is adverse compared to primary MIBC and whether NMIBC of higher risk of progression to MIBC is adverse compared to NMIBC of lower risk. Objective: Our objective was to assess cancer-specific survival (CSS) following radical cystectomy (RC) for primary MIBC and for NMIBC progressing to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 25 publications
1
37
0
1
Order By: Relevance
“…Aziz et al [4] showed that DSS did not differ significantly between both groups (p = 0.521) but when they classified progressive NMIBC according to EORTC risk score [3], they found that progressive NMIBC with a high score had a significantly shorter DSS compared to progressive NMIBC with intermediate EORTC score (p = 0.029). Similarly, de Vries et al [5] found no difference in survival between both groups with a 5-year DSS rate of 52% in the progressive group and 49% in the primary group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aziz et al [4] showed that DSS did not differ significantly between both groups (p = 0.521) but when they classified progressive NMIBC according to EORTC risk score [3], they found that progressive NMIBC with a high score had a significantly shorter DSS compared to progressive NMIBC with intermediate EORTC score (p = 0.029). Similarly, de Vries et al [5] found no difference in survival between both groups with a 5-year DSS rate of 52% in the progressive group and 49% in the primary group.…”
Section: Discussionmentioning
confidence: 99%
“…However, the oncological outcome of de novo vs. progressive MIBC patients after RC remains inconsistent in the literature, with varying and sometimes even with contradictory results regarding survival. Several authors have reported either similar or insignificantly different and comparable survival rates between the 2 groups [4,5,6,7,8,9,10,11]. Others have reported better survival in patients who progressed after initial presentation as NMIBC [12,13,14,] while yet others have reported worse prognosis if RC is performed in patients who progress to MIBC after having NMBIC [15,16.…”
Section: Introductionmentioning
confidence: 99%
“…In a study in relatively young patients (median age: 53 yr) without adjuvant chemotherapy, extended lymph node dissection (median of 49 vs 16 nodes removed) was associated with higher disease-free survival than standard lymphadenectomy, with a greater effect in node-positive patients [4]. Other authors found no relationship between the lymph node count and diseasespecific survival [5]. Extended and superextended lymph node dissection (median of 22 vs 38 nodes removed, respectively) was associated with virtually identical recurrence-free and overall survival rates [6].…”
Section: [ ( F I G _ 1 ) T D $ F I G ]mentioning
confidence: 95%
“…Secondary MIBC compared to primary MIBC could convey superior outcome because of the initial non-muscle invasive bladder cancer character or likewise convey inferior outcome because of its progressive tumor biology 7 , 8 , 13 , 22 . Meanwhile, similar prognosis was also reported in some studies 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%